Common woody plants and cacti of South Texas : a field guide - Taylor, Richard B. (Texas natural history guides., 2014)
Woody plants and cacti are vital staple foods for cattle, deer, and other wildlife in drought-prone South Texas. Ranchers, hunters, and land managers who need to identify these plants relied on A Field Guide to Common South Texas Shrubs (published by Texas Parks & Wildlife Press and distributed by UT Press), which is no longer in print. Responding to ongoing demand for the book, Richard B. Taylor has completely updated and expanded it with seven new species, new photographs, and a quick plant identification key. Common Woody Plants and Cacti of South Texas is an easy-to-use plant identification field guide to fifty species that comprise an estimated 90 percent of the region?s woody canopy cover north of the Rio Grande Valley. The species accounts include photographs, descriptions, values to livestock and wildlife, and nutritional information. The book also provides historical perspectives and information on brush management techniques and strategies, as well as habitat appraisal. All of these resources will enable readers to analyze stocking rates for deer and cattle, evaluate a prospective hunting lease, or buy property.